Social Cooperatives' Ways of Operation Activity in Poland — Some Features of Theory and Practice - Duraj, Jan (Comparative Economic Research. Central and Eastern Europe, 2011)
The social cooperative is one the newest organizational-legal forms of social enterprise. Its growth is caused by many determinants. One of them is the necessity of the prevention of social exclusion. Social cooperatives’ exceptionality is reflected in simultaneous realization of economic and social purposes but social goals owns the preference character. The paper is composed of three parts. Its first part contains deliberations about the concept itself and objectives of the social cooperative. They are presented against a wider background of human and social capital creation by enterprises. The second part deals with social and economic characteristics of the social cooperative. Finally, the third part contains fragmentary findings of empirical studies focused on the operation of social cooperatives in Poland. These findings cannot be treated, however, as sufficient to consider them a satisfactory recapitulation, and for this reason they should be treated as a preliminary diagnosis of analyzed problems accompanying the operation of social cooperatives in Poland.